Legal aspects of artificial intelligence and its application in the work of Police authorities - Delchev, Daniel (Law Journal of New Bulgarian University, 2022)
The application of artificial intelligence in the work of police structures is a relatively new aspect that is just entering the work of the police authorities worldwide. The Police cannot stay away from the deepening trends of digitalization and digital conversion in every detail of public life and related to it activities, including – reflecting on the way the authorities operate, on the procedures and on the organization of work of public authorities, along with the work of the police. This publication aims to analyze the main characteristics of artificial intelligence as a concept in its legal context, while at the same time presenting the trends in its implementation and giving examples of some good practices that could be applied by the Ministry of Interior in the Republic of Bulgaria.